Geographic Distribution of Foot and Ankle Orthopedic Surgeons Throughout the United States. Issue 2 (13th April 2021) - Fanelli, Matthew; Cush, Coleman; Zhang, Hui; Wagner, Benjamin; Young, Amanda J.; Grandizio, Louis Christopher; Cush, Gerard
Background: At present, the geographic distribution of orthopedic foot and ankle (OFA) surgeons in the United States is poorly defined. The purpose of this investigation is to determine the geographic distribution of OFA surgeons in the United States. We hypothesize that there will be differences in OFA surgeon density throughout the United States and that economic factors may play a role in access to subspecialty OFA care. Methods: A current membership list was obtained from the American Orthopaedic Foot & Ankle Society (AOFAS). Active members were categorized relative to states and US congressional districts, using publicly available census data. The relationship between income and surgeon density was determined using a Pearson correlation. Results: We identified a list of 1103 active AOFAS members. There was an average of 0.38 and 0.40 OFA surgeons per 100 000 people in each state and congressional district, respectively. We found a weak negative relationship demonstrating that regions with higher levels of poverty had fewer OFA surgeons, with a Pearson correlation coefficient of –0.14 (95% CI: –0.24, –0.04), P = .008. Conclusion: There is wide geographic variation of OFA surgeon density throughout the United States. Regions with higher levels of poverty were weakly associated with decreased population density of OFA surgeons compared to regions with lower poverty levels. Understanding these trends may aid in developing both recruitment and referral strategies for complex foot and ankle care in underserved regions. Level of Evidence: Level V.